Comperative studies of reinforcement concrete beam design using BS 8110 and ACI 318 - Ahmad Adli, Jamaludin (2010)
The application of reinforced concrete beam is a cheap and widely used in Malaysia. Therefore in order to cope with concrete development, a study has been carrying out. This study is basically to discover designs with economical purposes by using BS 8110 and ACI 318. In obtaining results, the value of moment and shear are set as constant. The scope of this study is on four various sizes of rectangular beams which are the beam size (500 mm x 450 mm, 600 mm x 350 mm, 650 mm x 500 mm, 700 mm x 400 mm). Microsoft Office Excel is used in this study in making the calculation easier and accurate. Microsoft Office Excel acts as a medium in obtaining results and there are also manual calculation being done to rake sure that the calculation using' Microsoft Office Excel is similar with the manuals. From analysis and result, it show that in order to get the area of reinforcement, ACT 318 is more economical while in spacing and link size, ACT 318 shows that it is more economical in term of number of link in used. From this findings, it shows that certain codes has it owns advantage and designer has options on it because all of these codes are still the same in terms of safety.